Analisis Pendapatan Asli Daerah (PAD) Kabupaten Kutai Kartanegara - Akhmadi Akhmadi; Syarifah Hudayah; Fitriadi Fitriadi (Owner : Riset dan Jurnal Akuntansi, 2023)
The Growth of Types of Income in Regional Taxes, Regional Retributions, Results of Separated Regional Wealth Management, and Other Legitimate Regional Original Revenues to Regional Original Revenues of Kutai Kartanegara Regency and (2) Quadrant Classification (Contribution and Growth) of Respectively Each Type of Income in Regional Taxes, Regional Levies, Separated Wealth Management Results, and Other Legitimate Regional Original Revenues Against Regional Original Income of Kutai Kartanegara Regency according to Klassen Typology. In this study, the research sources used secondary data from 2018-2021 obtained from: (1) Regional Financial and Asset Management Agency (BPKAD), and (2) Regional Revenue Agency (Bapenda) Kutai Kartanegara Regency. To analyze the secondary data, the Klassen Contribution, Growth and Typology analysis tools were used for each type of Regional Original Income of Kutai Kartanegara Regency to the total. The results of the analysis show that: (1) Based on the Contribution Analysis, Other Legitimate Regional Original Income is the type or source of revenue with the highest contribution to the total Regional Original Income during 2018-2021. (2) Based on the Growth Analysis, Regional Levies are the type or source of Regional Original Revenue with the highest growth during 2018-2021. (3) Based on Klassen's Typology Analysis, only Other PAD is able to provide opportunities to increase the total Regional Original Income of Kutai Kartanegara Regency during 2018-2021.